Interaction between antidepressant drugs and alcohol in university students (Research, Society and Development, 2021)
The use of medication associated with alcoholic substances is a problem, which pharmacy professionals are constantly faced with. This problem is even more accentuated when the medication has an antidepressant purpose, as interactions can present damage, from moderate to even Deaths.  In general, through a descriptive bibliographic research, based on 10 scientific articles, we sought to highlight the important considerations regarding the use of medication associated with alcohol in the university population.  The survey results showed that most students started using antidepressant medication after entering university, which demonstrates a relative illness in the academic community, generated by stress, demand, physical and mental overload, among other factors, thus, the authors highlight about this community, the great evidence of the use of alcohol and other substances, which, associated with antidepressants, can cause disastrous consequences.  It is noticed that there is a certain knowledge and awareness of students about the effects of using medication with alcoholic beverages, however, this evidence does not apply to efficiency so that there was a minimization of the practice.  The development of more studies by the scientific community is necessary, in order to unveil and expose to society greater contributions on the subject, in order to avoid the impacts generated by this practice.